Evaluating the Addition of a Clinical Pharmacist Service to a Midlevel Provider-Driven Culture Follow-up Program in a Community Emergency Department. (June 2021) - Rainess, Rebecca Ann; Patel, Vishal V.; Cavanaugh, Joseph Brian; Hill, Jessica
Background: The impact that an antimicrobial stewardship program can have on an inpatient setting has been well documented, but there are limited data on the use of an antimicrobial stewardship program in the emergency department (ED).Objective: The objective of this study was to assess the impact of adding a pharmacist service to a midlevel provider-driven culture follow-up program in the ED on achieving optimal therapy.Methods: This was a quasi-experimental study with designations of pre- and post-interventions conducted at a large community hospital with the pre-intervention phase occurring from June 1, 2019, to August 31, 2019, and the post-intervention phase occurring from January 1, 2020, to March 31, 2020. The primary outcome was optimal antimicrobial therapy: a composite of optimal antibiotic, dose, and duration, prescribed after the culture resulted. Secondary outcomes included optimal antibiotic, dose, duration, and return to the ED within 30 days due to infection.Results: Optimal antimicrobial therapy received after the culture resulted occurred in 59 patients (26.81%) in the pre-implementation phase and 40 patients (43.96%) in the implementation phase ( P = .003). For the secondary outcomes, optimal antibiotic choice occurred in 115 patients (52.27%) in the pre-implementation phase and 66 patients (72.53%) in the implementation phase ( P = .001). Optimal antibiotic dose occurred in 113 patients (51.36%) in the pre-implementation phase and 65 patients (71.43%) in the implementation phase ( P = .001). Optimal antibiotic duration occurred in 65 patients (29.55%) in the pre-implementation phase and 40 patients (43.96%) in the implementation phase ( P = .014).Conclusions: The addition of a clinical pharmacist service in a midlevel provider-driven ED culture callback program resulted in an increased rate of achieving optimal antimicrobial therapy.